Crosstalk between the cAMP-PKA pathway and the β-1,6-endoglucanase in Verticillium dahliae - EBOIGBE, Lugard; TZIMA, Aliki K.; PAPLOMATAS, Epaminondas J.; TYPAS, Milton A. (Phytopathologia Mediterranea, 2019)
In plant pathogenic fungi, different signalling pathways operate to control responses to nutrient availability during plant infection. A candidate from the cAMP-PKA signalling pathway, the cAMP-dependent protein kinase A gene, pkaC1, and the β-1,6-endoglucanase gene, vegB, involved in cell wall degradation, were studied in V. dahliae. Double mutants of the fungus were constructed, with insertional inactivation in the pkaC1 and vegB genes. Different developmental traits and virulence towards eggplant were evaluated in single and double disruption mutants. In all media tested, double mutants showed better radial growth but less conidia and microsclerotia than the wild type. An interaction between vegB and pkaC1 in controlling virulence on eggplants was recorded, as double mutants were slightly less virulent than the single mutant vegB- , but more virulent than the single mutant pkaC1-. Concomitant or independent function of the two genes and the signaling pathways they operate in for the different growth parameters and virulence are discussed.